Internal Model Disturbance Observer Based Continuous Non-singular Terminal Sliding Mode Control for Magnetic Levitation Systems - Lu, Qinkun; Jiang, Qinchen; Wang, Junxiao; He, Wei (Chinese Control Conference, 2022)
For attenuating the chattering phenomenon and improving the disturbance suppression for the magnetic levitation control system subject to multiple disturbances and parameter uncertainties, this paper proposes an internal model disturbance observer (IMDO) based continuous non-singular terminal sliding mode control (CNTSMC) scheme. Firstly, the magnetic levitation system with nonlinear dynamics is constructed. Then, ensuring the system position tracking performance and suppressing the chattering phenomenon, the use of the CNTSMC method makes the system state converge to the desired position in finite time. And, to improve the multiple disturbance rejection, an IMDO based CNTSMC scheme is designed for the system affected by multiple disturbances which include both high-order and trigonometric function forms. Compared with CNTSMC and CNTSMC+GPIO controllers, the results of simulation and experiment show that the proposed method can improve the performance of multiple disturbance rejection and position tracking.